Kinetics of Catalytic Oxidation of Carbenicillin: A Degradation Approach for Penicillanic Acid Derivatives (PADs) - Sahu, Yuv Raj; Dev, Rohit Kumar; Chaudhary, Narendra Kumar; Bhattarai, Ajaya (Journal of Nepal Chemical Society, 2023)
Diperiodatocuprate [DPC (III)] was selected to predict the kinetic studies for carbenicillin (CRBC) oxidation in the basic media. The investigation was completed in the presence of CoCl3 as catalyst by using a UV/Visible spectrophotometer at 298K temperature and 0.01 mol-dm-3 ionic strength which confirmed a 1:4 stoichiometry between CRBC and DPC (III). Both spectral and elemental analysis was used to identify the final products. Monoperiodatocuperate [MPC (III)] was found to be the primary active species of DPC (III). Pseudo-first order reaction was declared for DPC (III), while fractional order reactions were noticed in case of CRBC (substrate), Co (III) catalyst as well as KOH (alkali). However, for periodate, the reaction was determined to be in negative fractional order. Spectral evidence, determination of various rate constants, and both activation as well as thermodynamic parameters were used to predict plausible mechanism.